E-Modul Interaktif Aljabar Linier Menggunakan Flip PDF Professional - S, As Elly; Mulyono, Dodik (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to produce interactive linear algebra e-modules using the Professional Flip Pdf application for PGRI Lalupari University students that are valid, practical and effective. The method used in this research is Research and Development (R&D), which adopts the 4-D development model developed by Thiagarajan, Dorothy S. Semmel, and Melvyn I which generally consists of 4 stages, namely defining, designing, development, and disseminate. The results showed that the linear algebra interactive e-module met the valid aspects with an overall average score of 0.83 which was included in the very valid, practical criteria with an average score of 4.25 which was included in the very practical criteria and obtained a positive response by an average score of 4.28. The conclusions of the developed linear algebra interactive e-module are valid, practical and effective. Keywords: E-modul, Flip PDF Professional, Interaktif